2021
DOI: 10.1088/1361-665x/ac0b4c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical layout of shape memory alloy damping inerter (SDI) systems for vibration control

Abstract: A shape memory alloy damping inerter (SDI) with an SMA placed in parallel with an inerter and then in serial with a spring was developed as a vibration control device, where the inerter is utilized to amplify the deformation of SMA to improve the energy dissipation capacity. However, SDI can have other mechanical layouts when an SMA, an inerter and a spring are involved, which may exhibit different control effectiveness. Moreover, explicit design methods aiming to achieve the optimal performance of the SDI sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The experimental study showed that the proposed restrainer exhibits a stable energy dissipator with self-centering capability. Zhang et al [49] amplified the SMA deformation using different inerter mechanisms to improve its energy dissipation capacity and vibration mitigation. It was found that the SMA-spring-paralleled inerter system enhances damping characteristics and requires lesser SMA material.…”
Section: Ni-ti Smas In Energy Dissipative Systemsmentioning
confidence: 99%
“…The experimental study showed that the proposed restrainer exhibits a stable energy dissipator with self-centering capability. Zhang et al [49] amplified the SMA deformation using different inerter mechanisms to improve its energy dissipation capacity and vibration mitigation. It was found that the SMA-spring-paralleled inerter system enhances damping characteristics and requires lesser SMA material.…”
Section: Ni-ti Smas In Energy Dissipative Systemsmentioning
confidence: 99%
“…Structural vibration control techniques can effectively control the dynamic response of a structure under earthquake loads. [1][2][3][4][5][6][7][8] Based on many studies, energy dissipation devices can effectively reduce the structural vibration response caused by earthquake loads. 9,10 As a new type of energy dissipation and damping device, the inerter system has attracted much attention in the engineering field.…”
Section: Introductionmentioning
confidence: 99%
“…Pan and Zhang et al [29][30][31] proposed principles and methods for the optimal design of inerter system considering structural performance demand and control cost simultaneously based on random vibration theory. Subsequently, Zhang and Pan et al [32][33][34] discovered the principle of damping enhancement of the inerter system based on the analytical solution of the random vibration response, and the principle can provide a clear physical explanation of the mechanism of the inerter system.…”
Section: Introductionmentioning
confidence: 99%